(untitled) (International journal of artificial intelligence, 2024)
this article discusses the organization and outcomes of experimental work aimed at preparing future teachers to develop national and universal cultural competencies in students. The study highlights the significance of consistent, interconnected educational materials tailored to the capabilities of prospective teachers. Key directions include promoting theoretical and practical knowledge, revising educational programs, and integrating international research findings on education quality. The research outcomes informed the development of improved methodological resources and recommendations, which were tested and implemented in practice to enhance teacher preparation processes.